2017
DOI: 10.1371/journal.pone.0179332
|View full text |Cite
|
Sign up to set email alerts
|

Maternal BMI and diabetes in pregnancy: Investigating variations between ethnic groups using routine maternity data from London, UK

Abstract: ObjectiveTo investigate the ethnicity-specific association between body mass index (BMI) and diabetes in pregnancy, with a focus on the appropriateness of using BMI cut-offs to identify pregnant women at risk of diabetes.Study designAnalysis of routinely-collected data from a maternity unit in London, UK. Data were available on 53 264 women delivering between 2004 and 2012. Logistic regression was used to explore the association between diabetes in pregnancy and BMI among women of different ethnicities, and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 21 publications
(31 reference statements)
1
21
0
Order By: Relevance
“…The prevalence of diabetes in pregnancy was also estimated for each BMI cut‐off; results showed an increased risk of diabetes at all BMI points for South Asian women compared with White women . In addition, this study found that for South Asian women, the BMI with risk of GDM equivalent to 30 kg m −2 in White women was approximately 21 kg m −2 .…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…The prevalence of diabetes in pregnancy was also estimated for each BMI cut‐off; results showed an increased risk of diabetes at all BMI points for South Asian women compared with White women . In addition, this study found that for South Asian women, the BMI with risk of GDM equivalent to 30 kg m −2 in White women was approximately 21 kg m −2 .…”
Section: Resultsmentioning
confidence: 70%
“…These parameters gave an indication of the proportion of the population with GDM in each ethnic group that was captured using each cut‐off. A BMI of 20 kg m −2 captured 95.2% of White women compared with 95.0% of South Asian women with GDM . All other BMI cut‐offs investigated captured a higher percentage of South Asian women with GDM than White women .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations